2001
DOI: 10.1093/ije/30.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of acute leukaemia occurrence among children in the Chernobyl region

Abstract: Study results suggest that the increased risk of leukaemia and acute leukaemia among those children born in 1986 and resident in radioactively contaminated territories may be associated with exposure to radiation resulting from the Chernobyl accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
1
15
1
2
Order By: Relevance
“…It is known that radiation-induced cancer occurs more frequently in males, [72][73][74] yet the molecular grounds of this sex-specific bias are not well understood. The microRNA patterns observed in this study in the male and female spleen tissue may be used to further explore the molecular basis of sex differences in radiation-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that radiation-induced cancer occurs more frequently in males, [72][73][74] yet the molecular grounds of this sex-specific bias are not well understood. The microRNA patterns observed in this study in the male and female spleen tissue may be used to further explore the molecular basis of sex differences in radiation-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on childhood leukemia have been performed outside the former USSR [Auvinen et al, 1994;Hjalmars et al, 1994;Petridou et al, 1994;Parkin et al, 1996;Tondel et al, 1996], but none has shown any clear relationship to the fallout from the Chernobyl accident. However, exposure in utero has shown to increase the risk of leukemia significantly in Greece, Germany, and Ukraine [Petridou et al, 1996;Michaelis et al, 1997;Steiner et al, 1998;Noshchenko et al, 2001], but not in Belarus [Ivanov et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…Several ecologic studies have been reported of leukemia occurring among those exposed in utero (Petridou et al 1996;Ivanov et al 1998;Steiner et al 1998;Noshchenko et al 2001). None of these studies provide evidence for an association with leukemia with the possible exception of the Greek study (Petridou et al 1996), but in view of the ecologic nature of the studies and the generally small number of cases available for analysis, it cannot be said that this provides substantive evidence for a lack of association.…”
Section: Exposure In Uteromentioning
confidence: 95%